Pengaruh Motivasi, Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Anggota Polisi SAT Reskrim Polresta Padang - Alfian Alfian; Nindi Mujisi (JURNAL PUNDI, 2019)
Performance in an organization is considered important to achieve the goals and objectives set by the organization. To achieve such a professional performance in the police organization, especially on the Satrkrim Polresta Padang as which has been regulated by law, motivation is needed for each of its members. In all the national police organizations without exception and especially Sat Reskrim Polresta Padang has adopted a democratic leadership style which is based on eleven principles of Ki Hajar Dewantara. The variables described in the study are motivation (X1), leadership style (X2), work environment (X3) and employee performance (Y). The hypothesis described by the researcher is 1) the effect of motivation on performance, 2) the influence of leadership style on performance and 3) the influence of the work environment on performance. Based on the results of the study, the authors get conclusions which between motivation and leadership style both have a significant and positive effect on the performance of police members while for the work environment researchers get negative and not significant results on the performance of police members, especially members of the Sat Reskrim Polresta Padang.